Cutaneous Aβ-Non-nociceptive, but Not C-Nociceptive, Dorsal Root Ganglion Neurons Exhibit Spontaneous Activity in the Streptozotocin Rat Model of Painful Diabetic Neuropathy in vivo - Djouhri, Laiche; Zeidan, Asad; Abd El-Aleem, Seham A.; Smith, Trevor (Frontiers in Neuroscience, 2020)
Diabetic peripheral neuropathic pain (DPNP) is the most devastating complication of diabetes mellitus. Unfortunately, successful therapy for DPNP remains a challenge because its pathogenesis is still elusive. However, DPNP is believed to be due, at least partly, to abnormal hyperexcitability of dorsal root ganglion (DRG) neurons, but the relative contributions of specific functional subtypes remain largely unknown. Here, using the strepotozotocin (STZ) rat model of DPNP induced by a STZ injection (60 mg/kg, i.p), and intracellular recordings of somatic action potentials (APs) from DRG neurons in vivo, we examined electrophysiological changes in C-and A-nociceptive and Aα/-low threshold mechanoreceptive (LTM) neurons that may contribute to DPNP. We found in STZ-rats with established pain hypersensitivity (5 weeks post-STZ), compared with normal, several significant changes. These include: (a) increased incidence (by 23%) of spontaneous activity (SA) in Aα/-LTMs (but not C-mechanosensitive nociceptors) that may cause dysesthesias/paresthesia suffered by DPNP patients, (b) membrane hyperpolarization and a ~85% reduction in SA rate in Aα/-LTMs by Kv7 channel activation with retigabine (6 mg/kg, i.v.) suggesting that Kv7/M channels are involved in SA generation in this subpopulation of DRG neurons, (c) decreases in AP duration and in duration and amplitude of afterhyperpolarization (AHP) in C-and/or A-nociceptors. These faster AP and AHP kinetics may lead to repetitive firing and an increase in afferent input to the CNS and thereby contribute to DPNP development, and (d) a decrease in the electrical thresholds of A-nociceptors that may contribute to their sensitization, and thus to the resulting hypersensitivity associated with DPNP.